2011
DOI: 10.1029/2011jd016598
|View full text |Cite
|
Sign up to set email alerts
|

Monthly lunar declination extremes' influence on tropospheric circulation patterns

Abstract: [1] Short-term tidal variations occurring every 27.3 days from southern (negative) to northern (positive) maximum lunar declinations (MLDs), and back to southern declination of the moon have been overlooked in weather studies. These short-term MLD variations' significance is that when lunar declination is greatest, tidal forces operating on the high latitudes of both hemispheres are maximized. We find that such tidal forces deform the high latitude Rossby longwaves. Using the NCEP/NCAR reanalysis data set, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Support for the findings of Li et al [7] is provided by Krahenbuhl et al [8] who have shown that the 27.3 day lunar atmospheric tides can influence the short-term midlatitude general circulation pattern by deforming the highlatitude Rossby long-waves. They also find that these tidal effects have their greatest influence in the upper troposphere of both hemispheres.…”
Section: Introductionmentioning
confidence: 74%
“…Support for the findings of Li et al [7] is provided by Krahenbuhl et al [8] who have shown that the 27.3 day lunar atmospheric tides can influence the short-term midlatitude general circulation pattern by deforming the highlatitude Rossby long-waves. They also find that these tidal effects have their greatest influence in the upper troposphere of both hemispheres.…”
Section: Introductionmentioning
confidence: 74%
“…The differences in the behavior of the atmosphere with full versus new moon [ Shaffer et al ., ] and southern versus northern declination [ Krahenbuhl et al ., ] are previous work supported by these findings (points 3 and 4 above). These earlier findings further warrant the separate consideration of tidal potential associated with new versus full moon or northern versus southern MLD.…”
Section: Resultsmentioning
confidence: 99%
“…The change in the SAM may be due to Rossby wave breaking [ Wang and Magnusdottir , ; Ndarana et al ., ] associated with MLD as eluded to by Krahenbuhl et al . []. A positive influence associated with and following full moon with smaller MLD . Evidence (Figures and b) suggests that during Austral summer, a strong low‐latitudinal tidal forcing associated with full moon has a positive influence on the SAM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations